Nuove generazioni ed evoluzione dell’impresa familiare: la sfida della successione imprenditoriale. Analisi di alcuni casi di successo - Cesaroni, Francesca Maria; Sentuti, Annalisa (Piccola Impresa / Small Business, 2010)
This study focuses on the opportunities for change offered by inter-generational succession. We do not consider succession as a destabilizing event, possibly compromising the continuity and survival of the business, but rather as a condition favorable to the development of the small family-owned businesses. In this perspective, a classification of various types of change is proposed and some factors that could contribute to the activation of innovative dynamics are analyzed. The analysis of facilitating factors performed on fourteen successful cases show the importance of the following aspects: the successor’s training and his/her ability to manage change, the degree of openness of the predecessor, involvement in decision process of subjects outside the family, recourse to other family members (internal or external) and to other subjects, succession planning (even if not even formalized). Instead, transfer of ownership is not a decisive factor for the activation of innovative processes.